KEBIASAAN MAKAN SUKU ALUNE DENGAN HIPERURISEMIA - Rayanti, Rosiana Eva; Ubro, Maya Santika; Sasi, Galuh Ambar (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
Maluku Province has the highest incidence of hyperuricemia in Indonesia. The people of Maluku, including the Alune Tribe in Elpaputih Village, Seram Regency, have eating habits related to the local culture and traditions. Eating habits in hyperuricemia patients can trigger an increase or decrease in uric acid levels. The research aims to explore the eating habits of hyperuricemia patientsin the Alune tribe. The research method is descriptive qualitative. This research explores the eating habits among ten housewives. Criteria for participants are people with hyperuricemia in the family based on community health center data. Source triangulation used through community health center data on hyperuricemia, in-depth interviews, observation and thematic analysis. The results showed the concept of food, coconut milk as a favorite food and food setup for families with hyperuricemia. The food concept of the Alune Tribe is hereditary, putus asa, kumpul basudara, and bayah seram. Hereditary means the types of food are passed down from ancestors. Next, putus asa is introducing local foods such as papeda/sago porridge to children. Kumpul basudara is a symbol of brotherhood. Bayah seram concept is a particular tradition of the Alune people to prevent danger. Women have a position and role in food production with family food recipes from generation to generation, especially foods containing coconut milk. Women use food sources around the house and process them using firewood and a stove. Prevention of hyperuricemia through reducing food portions and food substitution. Tribal eating habits depend on cultural characteristics and geographic location.